Hubungan Antara Kemandirian Belajar dengan Hasil Belajar Kimia Kelas X MIPA di SMA Negeri 6 Pontianak - Valentina Winda Permata; Rachmat Sahputra; Erlina Erlina*; Rody Putra Sartika; Rahmat Rasmawan (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
Students' lack of independent learning results in low learning outcomes. This study is intended to determine the relationship between learning independence and chemistry learning outcomes for students in class X MIPA SMA Negeri 6 Pontianak. The subjects of this study were students in class X MIPA for the 2021/2022 academic year, totalling 130 persons. The research methodology used for this research is described using a correlational approach. The results of the chemistry studies are derived from the results of the final examination for the same semester 2021/2022. The data collection technique used is indirect communication in the form of questionnaires and literature reviews in the form of student learning results in chemistry subjects. The results showed that the average percentage of learning independence was 65% which were included in the medium category, while the average learning outcome was 62 which was included in the low category. The results of the Spearman rank test between learning independence and chemistry learning outcomes obtained a correlation coefficient of 0.079 which means that there is a positive, but very low relationship between learning independence variables and learning outcomes, the significance value obtained is 0.372 0.05, which means that there is no significant relationship significant relationship between independent learning with chemistry learning outcomes